Immersive Digital Data Asset as a Digital Preservation Model for Tangible and Intangible Culture Towards the Indonesia Archipelago Metaverse - Ida Bagus Ary Indra Iswara; Ida Bagus Gede Sarasvananda; Cokorda Pramartha (Malikussaleh University, Aceh, Indonesia, 2025)
This research embarks on a critical mission to develop and comprehensively evaluate the Immersive Digital Data Asset (IDDA) model, positing it as an innovative and robust cloud-based framework. This framework is meticulously designed for the digital preservation of Indonesia's exceptionally rich and diverse tangible and intangible cultural heritage, a crucial endeavor situated within the rapidly emerging and transformative landscape of the Indonesia Archipelago Metaverse. The study directly confronts and seeks to mitigate significant, persistent challenges prevalent in current cultural digitalization efforts across the nation. These challenges notably include the pervasive limited access to advanced technological infrastructure in many remote and underserved areas, compounded by the inherently high development and ongoing maintenance costs associated with cutting-edge immersive technologies. To achieve its objectives, this research rigorously employs a Systematic Literature Review (SLR) methodology. This approach allows for a meticulous analysis of existing academic trends, a systematic identification of crucial gaps within the current literature pertaining to digital cultural preservation, and a synthesis of best practices. The compelling findings unequivocally demonstrate the profound and multifaceted potential of the IDDA model. It serves not only as a powerful tool for safeguarding invaluable cultural assets from degradation and loss but also as a catalyst for fostering dynamic interdisciplinary research collaborations, both domestically and internationally. Furthermore, the model is shown to significantly stimulate the creative economy across Indonesia by enabling new forms of cultural expression and monetization within the digital realm. Nevertheless, the successful, widespread, and sustainable long-term implementation of the IDDA model is critically contingent upon substantial and concerted improvements in technological accessibility nationwide, ensuring equitable participation. This also necessitates a sustained, strategic, and collaborative investment from various stakeholders in its continuous development, infrastructure enhancement, and content creation to fully realize its transformative potential for Indonesia's cultural future.